Nilai-nilai Pendidikan dalam Cerita Anak Terbitan Harian Singgalang Edisi Minggu Periode 2011 - Ningsi, Oktria; Thahar, Harris Effendi; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2013)
This was a descriptive qualitative research which is aimed to describe and analyze educational values in Children’s Story published in Singgalang Daily Newspaper, Sunday Edition, 2011. There were four kinds of educational values; educational value of character, educational value of social care, educational value of intelligence, and educational value of religious. This research found that there were several educational values in this children story. They were not being defamatory, patient, tenderhearted and compassionate, obeying the rules, upright, fair, wise, shy, respectful, positive thinking, honest, talking politely, humble, asking for permission, do not take the right of others, care, feeling what others feel, mutual help, fear of being alone, becoming obedient citizen, cooperation, care to the environment, consensus and agreement, sharing with others, fasting critically, thinking logically, concluding critically, solving the problem creatively, elaborating problem critically, seeking halal sustenance, praying and thanking to the god, and welcomed the arrival of fasting time.